Fintech de crowdfunding: retos de su desarrollo en Perú - Cárdenas del Río, Yamilé (2021)
Worldwide fintech development is imminent. Nevertheless, Peru still does not have regulation that encourages the entry of fintechs to the Peruvian market and invigorates the sector. The bill that regulates crowdfunding is yet pending approval form Congress. If approved, the biggest challenges will be faced by the Peruvian Superintendence of Securities Market (Superintendencia del Mercado de Valores-SMV). A bigger financial inclusion with positive impact in the economy still seems distant, but it is starting.